Use of natural coagulants in the treatment of food industry effluent replacing ferric chloride: a review - Ferrari, Crislaine Trevisan da Rocha Ribeiro; Genena, Aziza Kamal; Lenhard, Daiane Cristina (Científica, 2016)
With increasing of world population food production has also increased to supply these needs. As a result of these factors have increased the use of natural resources, among them can be highlight that water after being used throughout the process eventually generates effluents with high pollutant load which if not properly treated can result in major environmental problems. To minimize this problem is used the treatment of these effluents and one of the mechanisms used is coagulation. The coagulants agents can be of chemical origin such as aluminum or iron, or natural origin, also called polyelectrolytes, such as moringa, chitosan and tannin. The advantages of using polyelectrolytes are numerous, they can be used in the effluents treatment from various industries, wastewater treatment and even drinking water treatment, in addition to their lower cost, higher efficiency, the lower volume of the sludge generated compared with the chemical coagulant, also its lower toxicity enables easier discharge and may even be used in agriculture as fertilizer.